Determinan Perilaku Penggunaan Kontrasepsi Pasca Persalinan di Wilayah Kerja Puskesmas Merdeka Kota Bogor - Agustina Agustina; Nawati Nawati (Politeknik Kesehatan Tanjung Karang, 2017)
Contraceptive use by women of reproductive age nationwide showed decreased from 61.4% (2007) to 55.86% (in 2010). In West Java amounted 59.8%. Unmet need in Indonesia is 14% and in West Java is 11.1%. Achievement of the family planning program active participant in Bogor reached 78.61% and the achievement of a new family planning program postpartum still low at 49.53% (BPMPM, Bogor 2013). The Purpose of research is to find out the determinant behavioral of contraceptive use post-natal in health center Bogor 2014.This research is quantitative with the design